AB1453-HPR Are dmard therapies effective on quality of life, anxiety and depression levels in patients with rheumatoid arthritis?. (12th June 2018) - Kinikli, G.I; Akar, F.; Demirtas, S.; Duman, M.A.; Ergin, S.; Gebes, M.E.; Guneser, Y.; Kinikli, G.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease with persistent joint inflammation manifesting as joint pain, stiffness, and swelling. Treatment of rheumatoid arthritis (RA) should be aimed at achieving the lowest possible disease activity. Conventional DMARDs (eg, methotrexate [MTX], hydroxychloroquine, and sulfasalazine) are still widely used in newly diagnosed RA patients. On the other hand, the rate of biologic therapy use in clinical practice is rising as more agents become available in spite of efficacy of these treatments is broadly comparable. Depression is a common under-recognised co-morbidity in patients with RA accompanying with substantial disability, reduced quality of life. Objectives: The aim of this study was to determine whether depression level is effected by response to therapy and compare the effectiveness of DMARD therapies in terms of quality of life, anxiety and depression levels in patients with RA. Methods: A total of 105 patients (Conventional DMARDs, n=67; Biological Therapy, n=38) with RA participated to the study. Disease activity was assessed using the Disease Activity Score in 28 joints (DAS28). Remission was defined as the absence of disease activity (i.e. tender joint count [TJC]=0+ swollen joint count [SJC]=0+ESR <10 mm/hr). The Hospital Anxiety and Depression Scale (HADS) was used to measure both anxiety and depression level. The Rheumatoid Arthritis Quality of Life (RAQoL) questionnaire was applied to assess quality of life. The drug therapy groups were compared using the Kruskal-Wallis test and the Chi-square test. Correlation between the scales was evaluated by Spearman's correlation coefficient. Results: There was no statistical difference in terms of RAQOL scores, disease activity and anxiety/depression scores between conventional DMARDs (RAQOL=16.78; DAS Remission=%46.3; Anxiety score=9.31; Depression score=7.34) and biological therapy (RAQOL=13.87; DAS Remission=%36.8; Anxiety score=8.24; Depression score=9.13) (p=0.096; p=0.816). RAQOL scores were significantly higher in patients with higher disease activity treated with conventional DMARDs (conventional DMARDs, DAS Activity=%43.3; biological therapy, DAS Activity=%39.5; RAQOL=17.54; p=0.006). RAQOL scores were statistically lower in patients with lower disease activity (p<0.001). Depression levels were statistically higher than anxiety levels (p=0.008). Conclusions: Our results demonstrated that the presence of depression coexisting with RA independent from disease activity may result in poorer clinical response to standard therapies. According to recent ACR recommendations, RA patients who may be candidates for biologics (eg, infliximab, etanercept, adalimumab) include patients with high disease activity, and those who have previously failed to respond adequately to conventional DMARD therapy. However, the results of the study suggest that different pharmacological therapies are not enough to improve quality of life in patients with RA. There is a need for certain non-pharmacological treatments integrated with medication management based on bio-psychosocial approaches to cope with depression in RA patients. References: [1] Matcham F, Ali S, Irving K, et al. Are depression and anxiety associated with disease activity in rheumatoid arthritis? A prospective study. BMC Musculoskelet Disord2016;17:155. doi:10.1186/s12891-016-1011-1 [2] Rathbun AM, Harrold LR, Reed GW. A prospective evaluation of the effects of prevalent depressive symptoms on disease activity in rheumatoid Arthritis Patients Treated with biologic response modifiers. Clin Ther2016;38:1759–72. doi:10.1016/j.clinthera.2016.06.007 Disclosure of Interest: None declared